تصميم جهاز لقياس شدة الإشعاع الشمسي المباشر (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
تم في هذا العمل تصميم وتصنيع جهاز صغير لقياس شدة الإشعاع الشمسي المباشر بطريقة بسيطة واقتصادية باستخدام مواد متوفرة محلياً، واستنتجت المعادلات الرياضية التي تمثل أساساً لإجراء القياسات على هذا الجهاز اعتماداً على الأثر الحراري التبادلي للإشعاع الشمسي المباشر في الجسم الأسود. أجريت قياسات عدّة لشدة الإشعاع الشمسي المباشر في أزمنة متعددة ضمن المنطقة المستهدفة, وقد تبين من خلال مقارنة نتائج هذه القياسات مع تلك المحسوبة نظرياً وجود تطابق جيد بينهما، وكما لوحظ أيضاً من خلال التحليل الرياضي للحسابات أنها تتميز بالسهولة المباشرة. In this work, a small device was designed and manufactured for measuring the intensity of direct solar radiation in a simple and economic method by using available local materials, and the mathematical equations that represent the basis for the measurements on this device were concluded depending on exchangeable thermal effect of direct solar radiation in the black body. Multiple measurements of the intensity of direct solar radiation in multiple times within the target area were made. It turned out by comparing the results of these measurements with those theoretically calculated there was a good match between them, as it was also noted through mathematical analysis of calculations they are characterized by direct easiness.